Effects of build orientation and element partitioning on microstructure and mechanical properties of biomedical Ti-6Al-4V alloy produced by laser sintering. (July 2017) - Mengucci, P.; Gatto, A.; Bassoli, E.; Denti, L.; Fiori, F.; Girardin, E.; Bastianoni, P.; Rutkowski, B.; Czyrska-Filemonowicz, A.; Barucca, G.
Abstract: Direct Metal Laser Sintering (DMLS) technology was used to produce tensile and flexural samples based on the Ti-6Al-4V biomedical composition. Tensile samples were produced in three different orientations in order to investigate the effect of building direction on the mechanical behavior. On the other hand, flexural samples were submitted to thermal treatments to simulate the firing cycle commonly used to veneer metallic devices with ceramics in dental applications. Roughness and hardness measurements as well as tensile and flexural mechanical tests were performed to study the mechanical response of the alloy while X-ray diffraction (XRD), electron microscopy (SEM, TEM, STEM) techniques and microanalysis (EDX) were used to investigate sample microstructure. Results evidenced a difference in the mechanical response of tensile samples built in orthogonal directions. In terms of microstructure, samples not submitted to the firing cycle show a single phase acicular α' (hcp) structure typical of metal parts subject to high cooling rates. After the firing cycle, samples show a reduction of hardness and strength due to the formation of laths of the β (bcc) phase at the boundaries of the primary formed α' plates as well as to lattice parameters variation of the hcp phase. Element partitioning during the firing cycle gives rise to high concentration of V atoms (up to 20 wt%) at the plate boundaries where the β phase preferentially forms. Graphical abstract: Element partitioning enriches the boundaries of α plates with V atoms where the formation of β phase starts (image a.). The β phase forms as laths not continuosly connected around the α plates (brither zones in image b). Highlights: Ti-6Al-4V alloy with improved mechanical properties are produced by DMLS. Build orientation influences the mechanical behaviour. Thermal treatments induce β phase formation at the α plate boundaries. Element partitioning is the main effect of thermal treatments.